A pump‐free microfluidic 3D perfusion platform for the efficient differentiation of human hepatocyte‐like cells. Issue 10 (27th June 2017) - Ong, Louis Jun Ye; Chong, Lor Huai; Jin, Lin; Singh, Pawan Kumar; Lee, Poh Seng; Yu, Hanry; Ananthanarayanan, Abhishek; Leo, Hwa Liang; Toh, Yi‐Chin
ABSTRACT: The practical application of microfluidic liver models for in vitro drug testing is partly hampered by their reliance on human primary hepatocytes, which are limited in number and have batch‐to‐batch variation. Human stem cell‐derived hepatocytes offer an attractive alternative cell source, although their 3D differentiation and maturation in a microfluidic platform have not yet been demonstrated. We develop a pump‐free microfluidic 3D perfusion platform to achieve long‐term and efficient differentiation of human liver progenitor cells into hepatocyte‐like cells (HLCs). The device contains a micropillar array to immobilize cells three‐dimensionally in a central cell culture compartment flanked by two side perfusion channels. Constant pump‐free medium perfusion is accomplished by controlling the differential heights of horizontally orientated inlet and outlet media reservoirs. Computational fluid dynamic simulation is used to estimate the hydrostatic pressure heads required to achieve different perfusion flow rates, which are experimentally validated by micro‐particle image velocimetry, as well as viability and functional assessments in a primary rat hepatocyte model. We perform on‐chip differentiation of HepaRG, a human bipotent progenitor cell, and discover that 3D microperfusion greatly enhances the hepatocyte differentiation efficiency over static 2D and 3D cultures. However, HepaRG progenitor cells are highly sensitive to the time‐point at which microperfusion is applied. Isolated HepaRG cells that are primed as static 3D spheroids before being subjected to microperfusion yield a significantly higher proportion of HLCs (92%) than direct microperfusion of isolated HepaRG cells (62%). This platform potentially offers a simple and efficient means to develop highly functional microfluidic liver models incorporating human stem cell‐derived HLCs. Biotechnol. Bioeng. 2017;114: 2360–2370. © 2017 Wiley Periodicals, Inc. Abstract : This study showcases a first instance of microfluidic 3D differentiation to generate functional hepatocyte‐like cells from a human liver progenitor cell (HepaRG). The microfluidic system was designed to maintain the liver progenitor cells in a 3D configuration under constant perfusion rate without the need of an external pump. This simplistic pump‐free system greatly facilitated long term perfusion culture and differentiation for up to 14 days. A 90% differentiation efficiency could be achieved under 3D microperfusion, which was significantly higher than static 2D and 3D differentiation configurations.